Sustainable intensification: What is its role in climate smart agriculture? - Campbell, Bruce M.; Thornton, Philip K.; Zougmoré, Robert B.; Asten, Piet J.A. van; Lipper, Leslie (Elsevier, 2014)
The ‘sustainable intensification’ (SI) approach and ‘climate-smart agriculture’ (CSA) are highly complementary. SI is an essential means of adapting to climate change, also resulting in lower emissions per unit of output. With its emphasis on improving risk management, information flows and local institutions to support adaptive capacity, CSA provides the foundations for incentivizing and enabling intensification. But adaptation requires going beyond a narrow intensification lens to include diversified farming systems, local adaptation planning, building responsive governance systems, enhancing leadership skills, and building asset diversity. While SI and CSA are crucial for global food and nutritional security, they are only part of a multi-pronged approach, that includes reducing consumption and waste, building social safety nets, facilitating trade, and enhancing diets.